Immunological Landscape of Non-Melanoma Skin Neoplasms: Role of CTLA4+IFN-γ+ Lymphocytes in Tumor Microenvironment Suppression - Silvana Karabatić Knezović; Dora Knezović; Jelena Ban; Antonela Matana; Neira Puizina Ivić; Merica Glavina Durdov; Mladen Merćep; Irena Drmić Hofman (Medicina)
Background and Objectives: This study explores the immunological landscapes of non-melanoma skin neoplasms (NMSNs), specifically keratoacanthoma (KA), squamous cell carcinoma (SCC), and common warts (VV). Although benign, KA shares histological similarities with low-grade SCC. The tumor microenvironment (TME) plays a key role in tumor progression, affecting angiogenesis, inflammation, and immune evasion. Viral infections, particularly human papillomavirus (HPV), are linked to NMSN development, with various HPV types identified in KA. VV, caused by HPV, serves as a comparative model due to its similar etiopathogenesis. Materials and Methods: This research examines the expression of CTLA4, a critical regulator of T-cell homeostasis, and IFN-γ, a cytokine with immunomodulatory and antiviral effects, in the TME of 41 KA, 37 SCC, and 55 VV samples using multichannel immunofluorescence. Results: The analysis revealed distinct patterns of CTLA4 and IFN-γ expression. SCC exhibited a higher prevalence of CTLA4+IFN-γ+ double-positive lymphocytes, suggesting a more immunosuppressive TME. In contrast, VV showed the highest expression of CTLA4+ cells, while both KA and VV had lower expressions of IFN-γ+ lymphocytes compared to SCC. The increased presence of CTLA4+IFN-γ+ double-positive lymphocytes in SCC suggests that the co-expression of these markers may exert a stronger effect on TME modulation than CTLA4 alone. Conclusions: These findings underscore the potential of immune profiling as a diagnostic tool to differentiate between benign and malignant lesions, such as KA and SCC. Furthermore, the presence of CTLA4+IFN-γ+ lymphocytes, particularly in SCC, may serve as a biomarker for tumor progression and a potential target for future immunotherapy strategies aimed at modulating the immune response in NMSN.